The microbioma and the human viroma: a new perspective within the oral and systemic pathologies. Bibliographic review - Fernández, Omaira (2020)
The present research is based on a bibliographic review that aimed to describe the characteristics of the microbiome and virome, and how their variations influence the health and disease process in the oral cavity of humans, for which the VHL virtual libraries and PubMed, as well as Scholar google and LILACS, were used as search words: microbiome, virome and oral cavity. A total of 58 articles were selected, both in English and Spanish, which fulfilled the inclusion criteria of having a maximum of 5 years of having been published at the time of the search. Observational, descriptive and explanatory studies were included, with value epidemiological, biological and methodological. It is concluded that there is published scientific evidence that supports that both the microbiome and the virome play an important role in health and disease processes, allowing dysbiosis to be analyzed, both orally and systemically. More studies are required to gain an in-depth understanding of this complex relationship and its impact on the health status of individuals.